Optimum fatigue performance of pre-stressed fastener holes - Shanmukha, N.; Vinod, M. S.; Murthy, C. S. Chandrashekara (Journal of Structural Engineering, 2025)
Cyclic stress concentration is a major source of fatigue cracking in the fastener holes which lead to fatigue life degradation. Hence pre-stressing of the fastener holes is used for fatigue life enhancement in engineering structures, which involves plastically deforming the material in both radial and hoop directions. This paper highlights the effect of prestressing by split sleeve cold expansion on the fatigue life of Aluminium-7050 and Mild Steel specimens. Specimens of varying extents of expansions were tested in Fatigue Machine under Low Cycle Fatigue (LCF). Experimentations revealed that the fatigue strength increases with higher percentages of expansion up to an optimum expansion and later decreases which is specimen dependant. The optimum expansion of the hole for maximizing fatigue life and stresses associated with the expansion were determined and have been compared with the photo elastic stress analysis, which is accomplished by analyzing through Reflection Polariscope. Finally, the variation of photo elasticity results with the Tresca yield criterion has been discussed.